Influence of nutritional status on rehabilitation efficacy of patients after stroke—a scoping review - Huan Chen; Caihong Fu; Weihao Fang; Zhenyao Wang; Dawei Zhang; Hu Zhang (Frontiers in Neurology)
Stroke patients are susceptible to malnutrition as a result of dysphagia, neurological impairments, and altered levels of consciousness. The nutritional status of individuals post-stroke is a critical determinant influencing the efficacy of rehabilitation outcomes. Therefore, there is great interest in the possible role of nutrients in promoting recovery after stroke. This article examines the enhancement of rehabilitation outcomes through the improvement of nutritional status. A comprehensive literature search was conducted using the PubMed, Cochrane, Web of Science, and Embase databases. Articles relevant to this topic, published from the inception of each database until November 2024, were identified. The selection was restricted to randomized controlled clinical trials, irrespective of language or publication date. The search specifically targeted studies involving stroke patients, encompassing both hemorrhagic and ischemic types, and interventions that combined nutritional supplementation with rehabilitation therapy. Studies with a focus on stroke prevention were excluded. Full-text articles that met the inclusion criteria were retrieved from the aforementioned sources. In instances where both a full report and a conference abstract were available for the same study, only the full report was considered. A total of 751 studies were considered for inclusion in this scoping review. Following a rigorous screening process, 13 studies were selected for detailed analysis. All selected studies were randomized controlled clinical trials. The findings indicate that supplementation with nutrients such as proteins, vitamins, essential amino acids, and antioxidants can enhance activities of daily living, improve balance function, and reduce neurological deficits in post-stroke patients. This review aims to synthesize current evidence regarding the effects of various nutrients and dietary regimens on limb rehabilitation in post-stroke patients, with the goal of providing new insights to facilitate the accelerated recovery of this population.